2020
DOI: 10.1101/2020.09.08.287979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Terminal Modification, Sequence, and Length Determine Small RNA Stability in Animals

Abstract: In animals, piRNAs, siRNAs, and miRNAs silence transposons, fight viral infections, and regulate gene expression. piRNA biogenesis concludes with 3′ terminal trimming and 2′-O-methylation. Both trimming and methylation influence piRNA stability. Here, we report that trimming and methylation protect mouse piRNAs from different decay mechanisms. In the absence of 2′-O-methylation, mouse piRNAs with extensive complementarity to long RNAs become unstable. In flies, 2′-O-methylation similarly protects both piRNAs a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 123 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Indeed, simultaneous deletion of both enzymes results in a higher frequency of 3′ tailing and stronger depletion of piRNAs than those of henn-1 or parn-1 single mutants. A recent pre-print revealed that both PNLDC1 (mouse homolog of PARN-1) and HENMT1 (mouse homolog of HENN-1) are required for the accumulation of piRNAs ( Gainetdinov et al, 2020 ). Together, these findings suggest that despite many differences in piRNA lengths and sequences in nematodes and mammals, the quality-control mechanism for piRNAs is nevertheless conserved.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, simultaneous deletion of both enzymes results in a higher frequency of 3′ tailing and stronger depletion of piRNAs than those of henn-1 or parn-1 single mutants. A recent pre-print revealed that both PNLDC1 (mouse homolog of PARN-1) and HENMT1 (mouse homolog of HENN-1) are required for the accumulation of piRNAs ( Gainetdinov et al, 2020 ). Together, these findings suggest that despite many differences in piRNA lengths and sequences in nematodes and mammals, the quality-control mechanism for piRNAs is nevertheless conserved.…”
Section: Discussionmentioning
confidence: 99%